Preparation method of fiberboard suitable for super-fluid static electricity powder spraying process
By adjusting the fiber diameter distribution and using melamine modified urea formaldehyde resin, combined with the cyclic hot pressing process and appropriate health time, the cracking problem of fiber boards in the superfluidic electrostatic powder spraying process is solved, the flatness and production efficiency of the board surface are improved, and the flatness and production efficiency are achieved. Higher product quality and stability.
Patent Information
- Application Number
- CN202411718648.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-28
AI Technical Summary
In the superfluidic static electropowder spraying process, fiber boards are prone to cracking due to high-temperature heating and curing, affecting the flatness and production efficiency of the panel surface.
By adjusting the fiber diameter distribution and glue application amount, the circulating hot pressing process and melamine-modified urea formaldehyde resin are used as the adhesive to control the plate density and health time to ensure the stability and strength of the fiber board under high temperature conditions.
It improves the flatness, moisture absorption resistance and production efficiency of fiberboard, reduces the risk of cracking, and improves product quality and stability.
Smart Images

Figure CN119260878A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiberboard production, and in particular relates to a method for preparing a fiberboard suitable for a superfluid static powder spraying process. Background Art
[0002] The traditional electrostatic powder processing of fiberboard is to perform sealing pretreatment on the edge and upper and lower surfaces of the board, then spray the powder coating, and then heat and cure it through infrared radiation at a certain temperature. The heating and curing temperature is usually 110-130℃ to form the required processed board. With the continuous improvement of people's living standards and aesthetics, higher requirements are also put forward for the board surface effect after spraying, such as the board surface after spraying should be smoother and flatter. In order to meet the current increasing customer needs, the super-leveling electrostatic powder spraying technology came into being. The super-leveling electrostatic powder spraying process can increase the temperature to 130-150℃ through a higher heating and curing temperature. High temperature can accelerate the spreading and curing of the powder coating on the board surface, thereby achieving the purpose of enhancing the flatness of the board surface coating and increasing the production speed. Increasing the heating and curing temperature will greatly increase the degree of heat applied to the board during the curing process. The moisture inside the board will escape faster during the heating process, causing impact on the inside of the board and causing cracking after powder spraying. Therefore, it becomes increasingly important to solve the problem of cracking of the board during superfluid static powder spraying. Summary of the invention
[0003] In view of the above shortcomings, the present invention discloses a method for preparing a fiberboard suitable for a superfluid static powder spraying process, which solves the problem that the board is prone to cracking after powder spraying when the board is subjected to the superfluidization process.
[0004] The present invention is achieved by adopting the following technical solutions: A method for preparing a fiberboard suitable for a superfluid static powder spraying process comprises the following steps: (1) Eucalyptus and miscellaneous wood are used as wood raw materials, and the weight ratio of eucalyptus to miscellaneous wood is (3-4): (6-7); the wood raw materials are processed to obtain fibers, in which fibers with a diameter of ≤0.06 mm account for 5-20% of the total weight, fibers with a diameter of 0.06-0.125 mm account for 25-40% of the total weight, fibers with a diameter of 0.125-1 account for 40-70% of the total weight, and fibers with a diameter of >1 mm account for 0.1-0.3% of the total weight; When the consistency of the thickness of the fibers constituting the board is poor, the coarse fibers will affect the smoothness of the board surface. The uneven thickness of the fibers will easily cause the path of water to be disordered during the heating process, resulting in uneven internal pressure and cracking at the weak points of the board. Therefore, the present invention adjusts the proportion of fibers with different diameters to make the coarse and thin fibers evenly matched to avoid the above problems. (2) Apply sizing to the fiber obtained in step (1) at a sizing amount of 290 to 300 kg / m 3 The adhesive used for gluing is urea-formaldehyde resin, and then the fibers are dried and laid out to form a fiberboard embryo.
[0005] (3) The fiberboard obtained in step (2) is subjected to a hot pressing process to obtain a board, wherein the density of the board is controlled to be 820-840 kg / m 3 , the core layer ratio is greater than 90% and the lowest point density of the core layer is greater than 730kg / m 3 The press pressure in the hot pressing process is 0.17-1.6 N / mm 2 , the speed is 135-235 mm / s, and the cyclic hot pressing method is adopted. The hot pressing temperature in the 1st to 3rd cycles is 220-245°C. The front area is lifted as much as possible to conduct the heat to the inside of the plate more effectively. The hot pressing temperature in the 4th to 6th cycles is 195-235°C. Under the premise of ensuring heat transfer, the adhesive is gradually cured to obtain the pressed plate; The appropriate board density can increase the density of the fiber without increasing the difficulty of subsequent fiberboard milling. The lowest point density of the core layer is controlled to be greater than 730kg / m 3 , ensuring that there are no weak points in the overall core layer; (4) After cooling the plate material after the hot pressing process in step (3), the plate material is stacked and stored for curing, and then subjected to conventional sanding and sawing to obtain a fiberboard suitable for the superfluid static discharge powder spraying process.
[0006] Furthermore, in step (1), the miscellaneous wood includes Quercus macrophylla, Oleander and Schima superba.
[0007] Furthermore, in step (4), after the plate is cooled to below 40°C, the plate is stacked and stored for 48 to 72 hours to obtain a fiberboard suitable for superfluid static powder spraying process. In the plate cooling process, after the plate comes out of the press, it is fully cooled by the joint action of multiple flap cooling wheels and three-dimensional forced convection cooling system, and the plate surface temperature (80 to 90)°C is ensured to be reduced to below 40°C before curing, so as to prevent the strength degradation of the plate due to insufficient dissipation of the residual heat of the plate. The curing storage process is to stack the plates and store them, and the curing cycle is guaranteed to be between 48 hours and 72 hours. First, the stress in the plate can be fully released, so that each component can reach a stable and balanced state; second, because the temperature of the middle part of the plate does not drop much during the stacking process, the appropriate curing time is ensured to minimize the degradation effect of the residual temperature of the plate on the plate.
[0008] Furthermore, in step (2), the urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, urea, melamine and polyvinyl alcohol in proportion; the weight of the melamine accounts for 3-8% of the total weight of the urea-formaldehyde resin, the molar ratio of the formaldehyde to the sum of urea and melamine is 0.85-0.95, and the weight of the polyvinyl alcohol accounts for 1-5% of the total weight of the urea-formaldehyde resin; S2, taking formaldehyde and placing it in a reaction kettle, adding caustic soda solution to adjust the pH value to 6.5-7.5, then adding melamine and stirring for 15-25 minutes, then heating to 60°C and measuring the pH value, when the pH value is 6.0-7.0, heating to 65°C and adding urea, and controlling the molar ratio of formaldehyde to urea to be 2.0-2.5 to obtain a mixture A; S3, taking the mixed material A obtained in step S2, heating it to 85-90°C and then heat-treating it for 20 minutes, then adding formic acid solution to adjust the pH value to 5.5-6.5, detecting the pH value and viscosity value every 5-10 minutes (measured by viscosity cup), when the viscosity reaches 18-20 seconds, adding caustic soda solution to adjust the pH value to 6.5-7.5, then adding urea and controlling the molar ratio of formaldehyde to urea to be 1.6-1.7, then stirring and reacting at 80-85°C, detecting the pH value and viscosity value every 5-10 minutes (measured by viscosity cup), and obtaining mixed material B when the viscosity reaches 20-22 seconds; S4, taking the mixture B obtained in step S3, adding caustic soda solution to adjust the pH value to 7.0-8.0, then adding urea and controlling the molar ratio of formaldehyde to urea to be 0.90-1.05, and then stirring for 10-20 minutes and adding polyvinyl alcohol to react to obtain a mixture C; The role of adding polyvinyl alcohol is not only that it can react with free formaldehyde to form polyvinyl alcohol formal with a six-membered ring structure, which is resistant to moisture and impact, but also that PVA molecules contain polar hydroxyl groups. PVA and polar plant fibers are cross-linked through hydrogen bonds to form a denser network structure, thereby enhancing the bonding strength between the adhesive and the fiber, thereby solving the problem of insufficient strength of the board due to baking at high temperatures during the super-leveling process, causing moisture in the board to escape and crack. It can also solve the problem of the board being exposed to the air and easily absorbing moisture in the air, reducing the risk of cracking of the board during the super-leveling process spraying; S5. The mixed material C obtained in step S4 is cooled to 45° C., and then a caustic soda solution is added to adjust the pH value to 8.0-8.5, and then cooled to below 40° C. and the viscosity is 16-20s and the solid content is 55.0-58.0% to obtain a melamine-modified urea-formaldehyde resin.
[0009] Furthermore, the concentration of the caustic soda solution is 25% to 35%, and the concentration of the formic acid solution is 15 to 20%.
[0010] Furthermore, in step S4, polyvinyl alcohol is added and reacted for 15 to 30 minutes to obtain a mixture C.
[0011] Compared with the prior art, this technical solution has the following beneficial effects: 1. The fiberboard prepared by the method of the present invention is conducive to engraving and milling processing. The board surface has good flatness after engraving and milling processing, so that after the board is sprayed with a super-leveling process, the paint surface becomes smooth and flat.
[0012] 2. The method of the present invention improves the moisture absorption resistance of the board, so that the board can be used normally in an environment with high humidity, thereby improving the stability of the product.
[0013] 3. The fiberboard prepared by the method of the present invention can meet the requirements of super-leveling electrostatic powder spraying under high temperature conditions, which greatly improves the production efficiency of electrostatic powder spraying, reduces the risk of product cracking, and improves product quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a comparative result diagram obtained from the moisture absorption test described in Experimental Example 1, wherein Curve 1 is the fiberboard obtained by the method described in Comparative Example 1, and Curve 2 is the fiberboard obtained by the method described in Example 1. DETAILED DESCRIPTION
[0015] The present invention is further described by the following examples, but is not intended to be limiting of the present invention. Specific experimental conditions and methods not specified in the following examples are conventional methods commonly known to those skilled in the art.
[0016] Embodiment 1: A method for preparing a fiberboard suitable for superfluid static powder spraying process, comprising the following steps: (1) Eucalyptus and miscellaneous wood are used as wood raw materials, and the weight ratio of eucalyptus to miscellaneous wood is 3.5:6.5; the wood raw materials are processed to obtain fibers, in which fibers with a diameter of ≤0.06 mm account for 10% of the total weight, fibers with a diameter of 0.06-0.125 mm account for 30% of the total weight, fibers with a diameter of 0.125-1 mm account for 59.8% of the total weight, and fibers with a diameter of >1 mm account for 0.2% of the total weight; the miscellaneous wood is a mixture of large-leaf oak, eucalyptus and magnolia; (2) Take the fiber obtained in step (1) and apply glue, the amount of glue applied is 295kg / m 3 The adhesive used for gluing is urea-formaldehyde resin, and then the fibers are dried and laid out to form a fiberboard embryo; (3) The fiberboard obtained in step (2) is subjected to a hot pressing process to obtain a board (a Dieffenbacher continuous press can be used, with an effective length of 42.88 m, a temperature range of 220-245° C., and a product specification of the board of 18-22 mm). The density of the board is 825 kg / m 3 The core layer ratio is 92% and the lowest point density of the core layer is 759kg / m 3 The press pressure in the hot pressing process is 0.17-1.6 N / mm 2 , the speed is 135-235 mm / s, and a cyclic hot pressing method is adopted, the hot pressing temperature in the 1st to 3rd cycles is 220-245°C, and the hot pressing temperature in the 4th to 6th cycles is 195-235°C; (4) After the plate material that has undergone the hot pressing process in step (3) is cooled to below 40° C., the plate material is stacked and stored for 60 hours to obtain a fiberboard suitable for a superfluid static discharge powder spraying process; The urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, urea, melamine and polyvinyl alcohol in proportion; the weight of the melamine accounts for 5% of the total weight of the urea-formaldehyde resin, the molar ratio of the formaldehyde to the sum of urea and melamine is 0.90, and the weight of the polyvinyl alcohol accounts for 3% of the total weight of the urea-formaldehyde resin; S2, taking formaldehyde and placing it in a reaction kettle, adding caustic soda solution to adjust the pH value to 7.0, then adding melamine and stirring for 20 minutes, then heating to 60°C and measuring the pH value, when the pH value is 6.5, heating to 65°C and adding urea, and controlling the molar ratio of formaldehyde to urea to be 2.2 to obtain a mixture A; the concentration of the caustic soda solution is 30%; S3, taking the mixed material A obtained in step S2, heating it to 86°C and then heat-treating it for 20 minutes, then adding formic acid solution to adjust the pH value to 6.0, detecting the pH value and viscosity value every 8 minutes (measured by viscosity cup), when the viscosity reaches 19 seconds, adding caustic soda solution to adjust the pH value to 7.0, then adding urea and controlling the molar ratio of formaldehyde to urea to be 1.64, then stirring and reacting at 80-85°C, detecting the pH value and viscosity value every 5-10 minutes (measured by viscosity cup), and obtaining mixed material B when the viscosity reaches 21 seconds; the concentration of the formic acid solution is 18%; S4, taking the mixture B obtained in step S3, adding caustic soda solution to adjust the pH value to 7.5-8.0, then adding urea and controlling the molar ratio of formaldehyde to urea to be 0.95, stirring for 15 minutes, adding polyvinyl alcohol and reacting for 20 minutes to obtain a mixture C; S5. The mixture C obtained in step S4 is cooled to 45° C., and then a caustic soda solution is added to adjust the pH value to 8.2, and then cooled to below 40° C. to obtain a melamine-modified urea-formaldehyde resin with a viscosity of 18s and a solid content of 56.0%.
[0017] Embodiment 2: A method for preparing a fiberboard suitable for superfluid static powder spraying process, comprising the following steps: (1) Eucalyptus and miscellaneous wood are used as wood raw materials, and the weight ratio of eucalyptus to miscellaneous wood is 4:6; the wood raw materials are processed to obtain fibers, in which fibers with a diameter of ≤0.06 mm account for 5% of the total weight, fibers with a diameter of 0.06-0.125 mm account for 25% of the total weight, fibers with a diameter of 0.125-1 mm account for 69.9% of the total weight, and fibers with a diameter of >1 mm account for 0.1% of the total weight; the miscellaneous wood includes a mixture of large-leaf oak, schisandra chinensis, and schisandra chinensis; (2) Take the fiber obtained in step (1) and apply glue, the amount of glue applied is 290kg / m 3 The adhesive used for gluing is urea-formaldehyde resin, and then the fibers are dried and laid out to form a fiberboard embryo; (3) The fiberboard obtained in step (2) is subjected to a hot pressing process to obtain a board having a density of 820 kg / m 3 The core layer ratio is 90% and the lowest density of the core layer is 738kg / m 3 The press pressure in the hot pressing process is 0.17-1.6 N / mm 2 , the speed is 135-235 mm / s, and a cyclic hot pressing method is adopted, the hot pressing temperature in the 1st to 3rd cycles is 220-235°C, and the hot pressing temperature in the 4th to 6th cycles is 195-228°C; (4) After the plate material that has undergone the hot pressing process in step (3) is cooled to below 40° C., the plate material is stacked and stored for 48 hours to obtain a fiberboard suitable for a superfluid static discharge powder spraying process; The urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, urea, melamine and polyvinyl alcohol in proportion; the weight of the melamine accounts for 3% of the total weight of the urea-formaldehyde resin, the molar ratio of the formaldehyde to the sum of urea and melamine is 0.85, and the weight of the polyvinyl alcohol accounts for 1% of the total weight of the urea-formaldehyde resin; S2, taking formaldehyde and placing it in a reaction kettle, adding caustic soda solution to adjust the pH value to 6.5, then adding melamine and stirring for 15 minutes, then heating to 60°C and measuring the pH value, when the pH value is 6.0, heating to 65°C and adding urea, and controlling the molar ratio of formaldehyde to urea to be 2.0 to obtain a mixture A; the concentration of the caustic soda solution is 30%; S3, taking the mixed material A obtained in step S2, heating it to 85°C and then heat-treating it for 20 minutes, then adding formic acid solution to adjust the pH value to 5.5, detecting the pH value and viscosity value every 5 minutes (measured by viscosity cup), when the viscosity reaches 18 seconds, adding caustic soda solution to adjust the pH value to 6.5, then adding urea and controlling the molar ratio of formaldehyde to urea to be 1.6, then stirring and reacting at 80-85°C, detecting the pH value and viscosity value every 5-10 minutes (measured by viscosity cup), and obtaining mixed material B when the viscosity reaches 20 seconds; the concentration of the formic acid solution is 15%; S4, taking the mixture B obtained in step S3, adding caustic soda solution to adjust the pH value to 7.0, then adding urea and controlling the molar ratio of formaldehyde to urea to be 0.90, stirring for 10 minutes, adding polyvinyl alcohol and reacting for 15 minutes to obtain a mixture C; S5. The mixed material C obtained in step S4 is cooled to 45° C., and then a caustic soda solution is added to adjust the pH value to 8.0. The mixed material C is then cooled to below 40° C. to obtain a melamine-modified urea-formaldehyde resin having a viscosity of 16s and a solid content of 55.0%.
[0018] Embodiment 3: A method for preparing a fiberboard suitable for superfluid static powder spraying process, comprising the following steps: (1) Eucalyptus and miscellaneous wood are used as wood raw materials, and the weight ratio of eucalyptus to miscellaneous wood is 3.6:6.2; the wood raw materials are processed to obtain fibers, in which fibers with a diameter of ≤0.06 mm account for 20% of the total weight, fibers with a diameter of 0.06-0.125 mm account for 40% of the total weight, fibers with a diameter of 0.125-1 mm account for 39.7% of the total weight, and fibers with a diameter of >1 mm account for 0.3% of the total weight; the miscellaneous wood is a mixture of Quercus macrophylla and Schima superba; (2) The fiber obtained in step (1) is sizing, and the sizing amount is 298 kg / m 3 The adhesive used for gluing is urea-formaldehyde resin, and then the fibers are dried and laid out to form a fiberboard embryo; (3) The plate obtained in step (2) is subjected to a hot pressing process to obtain a plate, wherein the density of the plate is controlled at 835 kg / m 3 The core layer ratio is 91% and the lowest density of the core layer is 760kg / m 3 The press pressure in the hot pressing process is 0.17-1.6 N / mm 2 , the speed is 135-235 mm / s, and a cyclic hot pressing method is adopted, the hot pressing temperature in the 1st to 3rd cycles is 235-240°C, and the hot pressing temperature in the 4th to 6th cycles is 215-220°C; (4) After the plate material having undergone the hot pressing process in step (3) is cooled to below 40° C., the plate material is stacked and stored for 66 hours to obtain a fiberboard suitable for superfluid static powder spraying process; The urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, urea, melamine and polyvinyl alcohol in proportion; the weight of the melamine accounts for 6% of the total weight of the urea-formaldehyde resin, the molar ratio of the formaldehyde to the sum of urea and melamine is 0.92, and the weight of the polyvinyl alcohol accounts for 4% of the total weight of the urea-formaldehyde resin; S2, taking formaldehyde and placing it in a reaction kettle, adding caustic soda solution to adjust the pH value to 7.0, then adding melamine and stirring for 20 minutes, then heating to 60°C and measuring the pH value, when the pH value is 6.5, heating to 65°C and adding urea, and controlling the molar ratio of formaldehyde to urea to be 2.4 to obtain a mixture A; the concentration of the caustic soda solution is 30%; S3, taking the mixed material A obtained in step S2, heating it to 88°C and then heat-treating it for 20 minutes, then adding formic acid solution to adjust the pH value to 6.0, detecting the pH value and viscosity value every 8 minutes (measured by viscosity cup), when the viscosity reaches 18.5s, adding caustic soda solution to adjust the pH value to 7.0, then adding urea and controlling the molar ratio of formaldehyde to urea to be 1.68, then reacting at 80-85°C, detecting the pH value and viscosity value every 5-10 minutes (measured by viscosity cup), and obtaining mixed material B when the viscosity reaches 21s; the concentration of the formic acid solution is 18%; S4, taking the mixture B obtained in step S3, adding caustic soda solution to adjust the pH value to 7.5, then adding urea and controlling the molar ratio of formaldehyde to urea to be 1.00, stirring for 15 minutes, adding polyvinyl alcohol and reacting for 25 minutes to obtain a mixture C; S5. The mixture C obtained in step S4 is cooled to 45° C., and then a caustic soda solution is added to adjust the pH value to 8.3. The mixture is then cooled to below 40° C. to obtain a melamine-modified urea-formaldehyde resin having a viscosity of 18s and a solid content of 57.0%.
[0019] Embodiment 4: A method for preparing a fiberboard suitable for superfluid static powder spraying process, comprising the following steps: (1) Eucalyptus and miscellaneous wood are used as wood raw materials, and the weight ratio of eucalyptus to miscellaneous wood is 3:7; the wood raw materials are processed to obtain fibers, among which fibers with a diameter of ≤0.06 mm account for 10% of the total weight, fibers with a diameter of 0.06-0.125 mm account for 29.8% of the total weight, fibers with a diameter of 0.125-1 mm account for 60% of the total weight, and fibers with a diameter of >1 mm account for 0.2% of the total weight; the miscellaneous wood includes large-leaf oak, eucalyptus and sibiricus; (2) Apply sizing to the fiber obtained in step (1) at a sizing amount of 300 kg / m 3 The adhesive used for gluing is urea-formaldehyde resin, and then the fibers are dried and laid out to form a fiberboard embryo; (3) The fiberboard obtained in step (2) is subjected to a hot pressing process to obtain a board having a density of 840 kg / m 3 The core layer ratio is 92% and the lowest density of the core layer is 740kg / m 3 The press pressure in the hot pressing process is 0.17-1.6 N / mm 2 , the speed is 135-235 mm / s, and a cyclic hot pressing method is adopted, the hot pressing temperature in the 1st to 3rd cycles is 225-245°C, and the hot pressing temperature in the 4th to 6th cycles is 210-235°C; (4) After the plate material that has undergone the hot pressing process in step (3) is cooled to below 40° C., the plate material is stacked and stored for 72 hours to obtain a fiberboard suitable for a superfluid static powder spraying process; The urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, urea, melamine and polyvinyl alcohol in proportion; the weight of the melamine accounts for 8% of the total weight of the urea-formaldehyde resin, the molar ratio of the formaldehyde to the sum of urea and melamine is 0.95, and the weight of the polyvinyl alcohol accounts for 5% of the total weight of the urea-formaldehyde resin; S2, taking formaldehyde and placing it in a reaction kettle, adding caustic soda solution to adjust the pH value to 7.5, then adding melamine and stirring for 25 minutes, then heating to 60°C and measuring the pH value, when the pH value is 7.0, heating to 65°C and adding urea, and controlling the molar ratio of formaldehyde to urea to be 2.5 to obtain a mixture A; the concentration of the caustic soda solution is 30%; S3, taking the mixed material A obtained in step S2, heating it to 90°C and then heat-treating it for 20 minutes, then adding formic acid solution to adjust the pH value to 6.5, detecting the pH value and viscosity value every 10 minutes (measured by viscosity cup), when the viscosity reaches 20s, adding caustic soda solution to adjust the pH value to 7.5, then adding urea and controlling the molar ratio of formaldehyde to urea to be 1.7, then reacting at 83-85°C, detecting the pH value and viscosity value every 5-10 minutes (measured by viscosity cup), and obtaining mixed material B when the viscosity reaches 22s; the concentration of the formic acid solution is 20%; S4, taking the mixture B obtained in step S3, adding caustic soda solution to adjust the pH value to 8.0, then adding urea and controlling the molar ratio of formaldehyde to urea to be 1.05, stirring for 20 minutes, adding polyvinyl alcohol and reacting for 30 minutes to obtain a mixture C; S5. The mixed material C obtained in step S4 is cooled to 45° C., and then a caustic soda solution is added to adjust the pH value to 8.5. The mixed material C is then cooled to below 40° C. to obtain a melamine-modified urea-formaldehyde resin having a viscosity of 20s and a solid content of 58.0%.
[0020] Comparative Example 1: The method for preparing a fiberboard suitable for superfluid static powder spraying process described in this comparative example differs from the method for preparing fiberboard described in Example 1 only in that the adhesive used in step (2) is conventional urea-formaldehyde resin, which is produced using urea and formaldehyde as raw materials.
[0021] Comparative Example 2: The preparation method of the fiberboard suitable for superfluid static powder spraying process described in this comparative example is different from the preparation method described in Example 1 only in that in step (2), the density of the board is 750 kg / m 3 The core layer ratio is 84% and the lowest density of the core layer is 630kg / m 3 .
[0022] Comparative Example 3: The preparation method of the fiberboard suitable for superfluid static powder spraying process described in this comparative example is different from the preparation method described in Example 1 only in that in step (2), the density of the board is 800 kg / m 3 The core layer ratio is 87% and the lowest density of the core layer is 696kg / m 3 .
[0023] Experimental Example 1: Fiberboard was produced according to the method described in Example 1 and Comparative Example 1, and then the fiberboard was subjected to an accelerated moisture absorption test in an environment of 36°C and 90% humidity, and the moisture absorption rate was calculated, that is, moisture absorption rate = (increased water mass / mass of the board after moisture absorption) × 100%. The specific results are shown in Figure 1 The fiberboard obtained by the present invention has good anti-hygroscopicity.
[0024] Experimental Example 2: Fiberboard was produced according to the method described in Examples 1 to 4 and Comparative Examples 1 to 3, and then the fiberboard was subjected to moisture absorption in an environment of 36°C and 90% humidity for 1h and 2h, and then baked at 150°C for 5min for testing. The specific results are shown in Table 1.
[0025] Table 1 Fiberboard baking test results
[0026] It can be seen from the data in Table 1 that the fiberboard prepared by the present invention has the characteristics of anti-hygroscopicity, high strength and excellent structural stability.
[0027] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a fiberboard suitable for superfluid static powder spraying process, characterized in that: The following steps are involved: (1) Eucalyptus and miscellaneous wood are used as wood raw materials, and the weight ratio of eucalyptus to miscellaneous wood is (3-4): (6-7); the wood raw materials are processed to obtain fibers, in which fibers with a diameter of ≤0.06 mm account for 5-20% of the total weight, fibers with a diameter of 0.06-0.125 mm account for 25-40% of the total weight, fibers with a diameter of 0.125-1 mm account for 40-70% of the total weight, and fibers with a diameter of >1 mm account for 0.1-0.3% of the total weight; (2) Apply sizing to the fiber obtained in step (1) at a sizing amount of 290 to 300 kg / m 3 The adhesive used for gluing is urea-formaldehyde resin, and then the fibers are dried and laid out to form a fiberboard embryo; (3) The fiberboard blank obtained in step (2) is subjected to a hot pressing process to obtain a board, wherein the density of the board is controlled to be 820-840 kg / m 3 , the core layer ratio is greater than 90% and the lowest point density of the core layer is greater than 730kg / m 3 The press pressure in the hot pressing process is 0.17-1.6 N / mm 2 , the speed is 135-235 mm / s, and a cyclic hot pressing method is adopted, the hot pressing temperature in the 1st to 3rd cycles is 225-240°C, and the hot pressing temperature in the 4th to 6th cycles is 200-232°C; (4) After cooling the plate material after the hot pressing process in step (3), the plate material is stacked and stored for curing, and then subjected to conventional sanding and sawing to obtain a fiberboard suitable for the superfluid static discharge powder spraying process.
2. The method for preparing a fiberboard suitable for superfluid static powder spraying process according to claim 1, characterized in that: In step (1), the miscellaneous wood includes Quercus macrophylla, Oleander and Schima superba.
3. The method for preparing a fiberboard suitable for superfluid static powder spraying process according to claim 1, characterized in that: In step (4), after the plate is cooled to below 40° C., the plate is stacked and stored for 48 to 72 hours to obtain a fiberboard suitable for superfluid static powder spraying process.
4. The method for preparing a fiberboard suitable for superfluid static powder spraying process according to claim 1, characterized in that: In step (2), the urea-formaldehyde resin is a melamine-modified urea-formaldehyde resin, and its preparation method comprises the following steps: S1. Weigh formaldehyde, urea, melamine and polyvinyl alcohol in proportion; the weight of the melamine accounts for 3-8% of the total weight of the urea-formaldehyde resin, the molar ratio of the formaldehyde to the sum of urea and melamine is 0.85-0.95, and the weight of the polyvinyl alcohol accounts for 1-5% of the total weight of the urea-formaldehyde resin; S2, taking formaldehyde and placing it in a reaction kettle, adding caustic soda solution to adjust the pH value to 6.5-7.5, then adding melamine and stirring for 15-25 minutes, then heating to 60°C and measuring the pH value, when the pH value is 6.0-7.0, heating to 65°C and adding urea, and controlling the molar ratio of formaldehyde to urea to be 2.0-2.5 to obtain a mixture A; S3, taking the mixed material A obtained in step S2, heating it to 85-90°C and then heat-treating it for 20 minutes, then adding formic acid solution to adjust the pH value to 5.5-6.5, detecting the pH value and viscosity every 5-10 minutes, when the viscosity reaches 18-20 seconds, adding caustic soda solution to adjust the pH value to 6.5-7.5, then adding urea and controlling the molar ratio of formaldehyde to urea to be 1.6-1.7, then stirring and reacting at 80-85°C, detecting the pH value and viscosity every 5-10 minutes, and obtaining mixed material B when the viscosity reaches 20-22 seconds; S4, taking the mixture B obtained in step S3, adding caustic soda solution to adjust the pH value to 7.0-8.0, then adding urea and controlling the molar ratio of formaldehyde to urea to be 0.90-1.05, and then stirring for 10-20 minutes and adding polyvinyl alcohol to react to obtain a mixture C; S5. The mixed material C obtained in step S4 is cooled to 45° C., and then a caustic soda solution is added to adjust the pH value to 8.0-8.5, and then cooled to below 40° C. and the viscosity is 16-20s and the solid content is 55.0-58.0% to obtain a melamine-modified urea-formaldehyde resin.
5. The method for preparing a fiberboard suitable for superfluid static powder spraying process according to claim 4, characterized in that: The concentration of the caustic soda solution is 25% to 35%, and the concentration of the formic acid solution is 15% to 20%.
6. The method for preparing a fiberboard suitable for superfluid static powder spraying process according to claim 4, characterized in that: In step S4, polyvinyl alcohol is added and reacted for 15 to 30 minutes to obtain a mixture C.
Citation Information
Patent Citations
Manufacturing process for ultra light fiber board
CN102806591A
Preparation method of E0-grade melamine modified urea formaldehyde resin
CN105348465A
E0 class low imbibitions routing fibreboard and production method thereof
CN107030841A
Modified urea-formaldehyde adhesive for applewood level E0 medium-density fiberboards and preparation method thereof
CN107151298A
Production method of special highly-moisture-proof intermediate-density fiber board for office table
CN109129755A